2019
DOI: 10.1089/thy.2018.0754
|View full text |Cite
|
Sign up to set email alerts
|

Fingolimod Improves the Outcome of Experimental Graves' Disease and Associated Orbitopathy by Modulating the Autoimmune Response to the Thyroid-Stimulating Hormone Receptor

Abstract: Graves' disease and Graves´ orbitopathy are associated with stimulating thyrotropin receptor (TSHR) autoantibodies and autoreactive T cells. Recent in vitro studies suggested sphingosine-1-phosphate (S1P) signaling is involved in orbitopathy. In the current study we explored the immune modulatory potential of S1P receptor antagonist fingolimod in a murine model for Graves' disease. Fingolimod was orally administered preventively during disease onset or therapeutically after disease onset. Administration of fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Studies in GO murine models also supported T cell-mediated inflammation in the orbit in vivo . CD3 + total T cells were found to infiltrate into the orbital muscles and periorbital tissues of human (h) TSHR-A subunit plasmid-immunized BALB/c mice ( 35 , 46 ). The same phenomenon was found in mouse TSHR-A subunit plasmid-immunized BALB/c mice ( 47 ).…”
Section: Cd4 + and Cd8 + T Cellmentioning
confidence: 99%
“…Studies in GO murine models also supported T cell-mediated inflammation in the orbit in vivo . CD3 + total T cells were found to infiltrate into the orbital muscles and periorbital tissues of human (h) TSHR-A subunit plasmid-immunized BALB/c mice ( 35 , 46 ). The same phenomenon was found in mouse TSHR-A subunit plasmid-immunized BALB/c mice ( 47 ).…”
Section: Cd4 + and Cd8 + T Cellmentioning
confidence: 99%
“…In the future thyroid specialists should consider immunosuppressive/immunomodulatory therapy not only for patients with severe GO but possibly also for patients which reach the cut off for relapse to improve the prognosis for ATD therapy, because it has been shown with the serial evaluation that once a patient reaches the relapse zone the probability to switch in the remission group is almost zero. Immunotherapeutic options have been recently tested to be effective in treating autoimmune hyperthyroidism as well in a GD mouse model [33].…”
Section: Cut Off Levels For Predictions Of Relapse During the Course mentioning
confidence: 99%
“…With respect to this, our study is limited since it did not investigate Treg populations expressing Foxp3 which could have been differently affected by the antibiotic treatment. A few studies addressed the role of Treg expressing FoxP3 in GD/GO mouse models [33][34][35][36]. In a GD mouse model induced by adenovirus Ad-TSHR289, the frequencies of CD4+CD25+Foxp3+ Treg cells were decreased [34,36].…”
Section: • Fibroblastsmentioning
confidence: 99%
“…Another recent in vitro study suggested that sphingosine-1-phosphate (S1P) signaling is involved in orbitopathy [13]. In a follow-up study the immune modulatory potential of S1P receptor antagonist fingolimod (FTY720) was explored in a murine model for Graves' disease [33]. In the model TSHR autoimmunity was induced by immunization with a plasmid encoding for the A-subunit of the TSHR.…”
Section: Treatment Studies With In Vivo Models Of Go-translation Intomentioning
confidence: 99%
See 1 more Smart Citation